FROM THE HISTORY OF ORGANIZATION OF AIR FLEET AND INTRODUCTION OF PLANES (Scientific journal of the Fergana State University, 2023)
This article describes the work done in Bukhara in 1920-1924 on the organization of the air fleet, the organization of air traffic through the analysis of primary sources and literature.